Seasonal malaria chemoprevention in an area of extended seasonal transmission in Ashanti, Ghana: an individually randomised clinical trial. Issue 2 (16th December 2015) - Tagbor, Harry; Antwi, Gifty Dufie; Acheampong, Princess Ruhama; Bart Plange, Constance; Chandramohan, Daniel; Cairns, Matthew
Abstract: Objective: To investigate the effectiveness of seasonal malaria chemoprevention (SMC) and community case management with long‐acting artemisinin‐based combination therapies (ACTs) for the control of malaria in areas of extended seasonal malaria transmission. Method: Individually randomised, placebo‐controlled trial in the Ashanti Region of Ghana. A total of 2400 children aged 3–59 months received either: (i) a short‐acting ACT for case management of malaria (artemether‐lumefantrine, AL) plus placebo SMC, or (ii) a long‐acting ACT (dihydroartemisinin‐piperaquine, DP) for case management plus placebo SMC or (iii) AL for case management plus active SMC with sulphadoxine‐pyrimethamine and amodiaquine. SMC or placebo was delivered on five occasions during the rainy season. Malaria cases were managed by community health workers, who used rapid diagnostic tests to confirm infection prior to treatment. Results: The incidence of malaria was lower in children given SMC during the rainy season. Compared to those given placebo SMC and AL for case management, the adjusted hazard ratio (aHR) was 0.62 (95% CI: 0.41, 0.93), P = 0.020 by intention to treat and 0.53 (95% CI: 0.29, 0.95), P = 0.033 among children given five SMC courses. There were no major differences between groups given different ACTs for case management (aHR DP vs . AL 1.18 (95% CI 0.83, 1.67), P = 0.356). Conclusion: SMC may have an important public health impact in areas with a longer transmission season, but further optimisation of SMC schedules is needed to maximise its impact in such settings.